Beef intake and risk of rheumatoid arthritis: Insights from a cross-sectional study and two-sample Mendelian randomization - Chen, Weiwei; Liu, Ke; Huang, Lin; Mao, Yingying; Wen, Chengping; Ye, Ding; He, Zhixing (Frontiers in Nutrition, 2022)
Background: Beef is common in daily diet, but its association with the risk of rheumatoid arthritis (RA) remains uncertain. The objective of this study is to explore the relationship between beef intake and the risk of RA. Methods: We investigated the association between beef intake and risk of RA by multivariate logistic regression, based on the National Health and Nutrition Examination Survey (NHANES) 1999-2016 involving 9618 participants. The dose-response relationship between beef intake and RA was explored as well. Furthermore, we performed Mendelian randomization (MR) analysis to examine the causal effect of beef intake on RA. Genetic instruments for beef intake were selected from a genome-wide association study (GWAS) including 335,576 individuals from the UK Biobank study, and summary statistics relating to RA were obtained from a GWAS meta-analysis of 14,361 RA patients and 43,923 controls. The inverse-variance weighted (IVW) approach was used to estimate the causal association, and MR-Egger regression and Mendelian randomization pleiotropy residual sum and outlier (MR-PRESSO) test were applied to evaluate the pleiotropy and outliers. Results: Compared with the lowest quintile (0 to ≤33.50 g/d), beef intake was found to be significantly associated with risk of RA (odds ratio [OR]: 1.94; 95% confidence interval [CI]: 1.20 to 3.12) in the third quintile (50.26 g/d to ≤76.50 g/d). Moreover, a reversed “U” dose-response relationship between beef and RA (Pnon-linearity =0.023) was found. In the MR analysis, beef intake was associated with an increased risk of RA (OR: 3.05; 95% CI: 1.11 to 8.35; P=0.030) by the IVW method. The results from MR-Egger regression and MR-PRESSO test showed that there were no pleiotropic variations and outliers. Conclusion: This study indicated that there is suggestive evidence to support the causal effect of beef intake on risk of RA, while further studies are warranted to elucidate the exact association.